IVRS BASED COLLEGE AUTOMATION (International Journal of Engineering and Computer Science, 2014)
An Interactive Voice Response is a system based on telephone which allows users to enter information and make menu selections using dual-tone multi-frequency (DTMF) signaling. Interaction of users is done with a computer by using their telephone as a terminal. The objective of the system is to reform the services provided to users by get rid of an operator. An IVR can be tailored to the particular needs of an organization, depending on information contained in database. An IVRS is righteous for handling repetitious enquiries.